First cardiovascular event in patients with type 2 diabetes mellitus of a cardiovascular risk management program of a poor colombian population: a cohort study (2018)
Background: According to several studies in population of high-income countries (HIC), patients with Type 2 diabetes mellitus (DM) have a considerably higher risk of cardiovascular morbidity and mortality. However, it is not clear if the magnitude of this association can be widespread in other populations. The objective of this study was to determine the independent association between Type 2 DM and first cardiovascular event in Colombian Caribbean poor population with no records of previous cardiovascular events reported. Methods: We retrospectively reviewed the individual records from the hospitalizations database of 64,668 patients of cardiovascular risk management program from July 2014 to December 2015. We used a propensity score matching cohort analysis for this study. The Kaplan–Meier curves were constructed for the cardiovascular events related endpoints and matched Cox-regression analysis to estimate associations of a history of Type 2 DM with cardiovascular outcomes during 1.5 years of follow-up. A formal sensitivity analysis using The Breslow-Day and Tarone Homogeneity tests was conducted. Results: Out of 56,351 patients with no previous cardiovascular events records, 19,368 (34.4%) patients were found to suffer Type 2 DM. Using propensity scores for Type 2 DM, we gathered a cohort of 18,449 pairs of patients with and without Type 2 DM who were balanced on 22 baseline characteristics. A first cardiovascular event occurred in 650 (3.5%) and 403 (2.1%) matched patients with and without Type 2 DM, respectively, during 1.5 years of followup. Type 2 DM was associated with first cardiovascular event (HR 1.69; 95% CI 1.43–2.00; p = 0.000), AMI (HR 1.79; 95% CI 1.45–2.20; p = 0.000) and stroke (HR 1.54; 95% CI 1.18–2.02; p = 0.001). Hazard ratios (95% CIs) for the association of Type 2 DM with all-cause mortality, cardiovascular mortality and all-cause hospitalization were 1.36 (1.21–1.53; p < 0.001), 1.52 (1.12–2.08; p 0.004), and 1.20 (1.21–1.53; p < 0.001), respectively. Conclusion: Type 2 DM resulted to be a significant independent risk factor for first cardiovascular event in Colombian Caribbean poor population with no previous records of cardiovascular events.